In situ delivery of iPSC-derived dendritic cells with local radiotherapy generates systemic antitumor immunity and potentiates PD-L1 blockade in preclinical poorly immunogenic tumor models. Issue 5 (28th May 2021) - Oba, Takaaki; Makino, Kenichi; Kajihara, Ryutaro; Yokoi, Toshihiro; Araki, Ryoko; Abe, Masumi; Minderman, Hans; Chang, Alfred E; Odunsi, Kunle; Ito, Fumito
Abstract : Background: Dendritic cells (DCs) are a promising therapeutic target in cancer immunotherapy given their ability to prime antigen-specific T cells, and initiate antitumor immune response. A major obstacle for DC-based immunotherapy is the difficulty to obtain a sufficient number of functional DCs. Theoretically, this limitation can be overcome by using induced pluripotent stem cells (iPSCs); however, therapeutic strategies to engage iPSC-derived DCs (iPSC-DCs) into cancer immunotherapy remain to be elucidated. Accumulating evidence showing that induction of tumor-residing DCs enhances immunomodulatory effect of radiotherapy (RT) prompted us to investigate antitumor efficacy of combining intratumoral administration of iPSC-DCs with local RT. Methods: Mouse iPSCs were differentiated to iPSC-DCs on OP9 stromal cells expressing the notch ligand delta-like 1 in the presence of granulocyte macrophage colony-stimulating factor. Phenotype and the capacities of iPSC-DCs to traffic tumor-draining lymph nodes (TdLNs) and prime antigen-specific T cells were evaluated by flow cytometry and imaging flow cytometry. Antitumor efficacy of intratumoral injection of iPSC-DCs and RT was tested in syngeneic orthotopic mouse tumor models resistant to anti-PD-1 ligand 1 (PD-L1) therapy. Results: Mouse iPSC-DCs phenotypically resembled conventional type 2 DCs, and had a capacity to promote activation, proliferation and effector differentiation of antigen-specific CD8 + T cells in the presence of the cognate antigen in vitro. Combination of in situ administration of iPSC-DCs and RT facilitated the priming of tumor-specific CD8 + T cells, and synergistically delayed the growth of not only the treated tumor but also the distant non-irradiated tumors. Mechanistically, RT enhanced trafficking of intratumorally injected iPSC-DCs to the TdLN, upregulated CD40 expression, and increased the frequency of DC/CD8 + T cell aggregates. Phenotypic analysis of tumor-infiltrating CD8 + T cells and myeloid cells revealed an increase of stem-like Slamf6 + TIM3 − CD8 + T cells and PD-L1 expression in tumor-associated macrophages and DCs. Consequently, combined therapy rendered poorly immunogenic tumors responsive to anti-PD-L1 therapy along with the development of tumor-specific immunological memory. Conclusions: Our findings illustrate the translational potential of iPSC-DCs, and identify the therapeutic efficacy of a combinatorial platform to engage them for overcoming resistance to anti-PD-L1 therapy in poorly immunogenic tumors.